2018
DOI: 10.1055/s-0038-1651495
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous Mycobacteria in Cystic Fibrosis

Abstract: Nontuberculous mycobacteria (NTM) can cause chronic pulmonary infection in susceptible hosts. Individuals with cystic fibrosis (CF), a multisystem disease predominated by progressive structural lung disease, are particularly vulnerable. Only recently have NTM been recognized for their potential to cause lung deterioration in CF patients. The reported prevalence varies widely from 4 to 40%, significantly more common than in the general population, but this varies because of multiple factors including inconsiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 91 publications
1
5
0
Order By: Relevance
“…Here, we have reproduced Mabs infection hallmarks in AOs in healthy and CF contexts. Specifically, we show that both S-and R-Mabs replicate as extracellular bacteria in AOs, which was further enhanced in CF context, thus recapitulating the susceptibility of CF patients to NTM infection [54,55] and consistent with Mabs localization in the airway of CF patients [56]. We showed that Mabs S is surrounded by an extracellular substance resembling a biofilm.…”
Section: Plos Pathogenssupporting
confidence: 66%
“…Here, we have reproduced Mabs infection hallmarks in AOs in healthy and CF contexts. Specifically, we show that both S-and R-Mabs replicate as extracellular bacteria in AOs, which was further enhanced in CF context, thus recapitulating the susceptibility of CF patients to NTM infection [54,55] and consistent with Mabs localization in the airway of CF patients [56]. We showed that Mabs S is surrounded by an extracellular substance resembling a biofilm.…”
Section: Plos Pathogenssupporting
confidence: 66%
“…Currently, most clinical laboratories have systems which operate in positive ion mode only. Where this is the case, a combination of inexpensive rapid antigen testing (MBT64) combined with lipidomic MALDI-ToF analysis would provide definitive TB identification (TB or not TB, and likely NTM species) rapidly and cheaply in all clinical laboratories and provide species-level identification for NTMs which can have immediate management implications in certain populations (cystic fibrosis, non-cystic fibrosis bronchiectasis, cardiothoracic surgery, immunosuppressed individuals) [ [42] , [43] , [44] , [45] , [46] ].…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterial infections impose a substantial global health burden, and drug resistance in Mycobacterium tuberculosis and non-tuberculous mycobacteria (NTM) is widespread1 , 2. Cystic Fibrosis (CF) patients frequently have NTM infections, including Mycobacterium abscessus 3 , 4, which are antibiotic resistant and difficult to manage clinically3 , 5. CF is the third most common indication for lung transplantation, but persistent infection – particularly when NTM are present prior to surgery – can result in substantial post-transplant morbidity and mortality4 , 6 , 7.…”
mentioning
confidence: 99%
“…Cystic Fibrosis (CF) patients frequently have NTM infections, including Mycobacterium abscessus 3 , 4, which are antibiotic resistant and difficult to manage clinically3 , 5. CF is the third most common indication for lung transplantation, but persistent infection – particularly when NTM are present prior to surgery – can result in substantial post-transplant morbidity and mortality4 , 6 , 7. Therapeutic bacteriophages are a plausible alternative treatment to antibiotics8, but have not been used for mycobacterial infections in humans911; personalized intravenous phage treatments for other bacterial infections have been described (Supplemental Information)12 , 13.…”
mentioning
confidence: 99%